On the construction of mixed-level rotatable response surface designs when experimental unit experiences overlap effects. Issue 5 (4th May 2023) - Verma, Ankita; Jaggi, Seema; Varghese, Eldho; Varghese, Cini; Bhowmik, Arpan; Datta, Anindita; M, Hemavathi
Abstract: This paper describes the response surface model for mixed-level factors of the form 2 n ×3 where experimental units/plots experience the overlap effects from immediate left and right neighboring units. Conditions have been derived for the orthogonal estimation of the parameters of the model. A method of constructing mixed-level response surface designs of the form 2 n ×3 has been proposed. The designs developed satisfy the derived conditions of rotatability. Further, the method has been extended to the case of mixed-level rotatable designs of the form 2 n ×3 n . An algorithm for the estimation of overlap effects has also been discussed, along with an illustration.